Analisis Manajemen Laba Memediasi Saat Pengimplementasian Tata Kelola dan Pengungkapan Tanggungjawab Sosial Terhadap Kinerja Keuangan Perusahaan Manufaktur Sektor Industri Dasar dan Kimia - Endang Ranitawati; Yahya Yahya (Jurnal of Management and Social Sciences, 2024)
The aim of this research is to prove empirically that earnings management mediates the implementation of corporate governance relationships and disclosure of corporate social responsibility in influencing the financial performance of manufacturing companies in the basic and chemical industry sectors listed on the IDX for the 2019 - 2022 period, either directly or indirectly. The proposed research problem refers to previous research and the existence of research gaps in previous research. In this research, seven hypotheses have been formulated using a purposive sampling method and using secondary data obtained from annual reports published by the BEI. Based on existing criteria, a sample of 31 manufacturing companies in the basic industrial and chemical sectors were "listed" on the IDX for the 2018 - 2021 period. This research shows the results obtained based on Partial Least Square - Structural Equation Model (PLS-SEM) analysis in the SmartPLS 3.0 program . The research results show that corporate governance has a significant positive influence on the company's financial performance.